2010
DOI: 10.1098/rspb.2010.1856
|View full text |Cite
|
Sign up to set email alerts
|

Antipodean white sharks on a Mediterranean walkabout? Historical dispersal leads to genetic discontinuity and an endangered anomalous population

Abstract: The provenance of white sharks (Carcharodon carcharias) in the Mediterranean is both a conundrum and an important conservation issue. Considering this species's propensity for natal philopatry, any evidence that the Mediterranean stock has little or no contemporary immigration from the Atlantic would suggest that it is extraordinarily vulnerable. To address this issue we sequenced the mitochondrial control region of four rare Mediterranean white sharks. Unexpectedly, the juvenile sequences were identical altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 37 publications
(66 reference statements)
1
61
1
Order By: Relevance
“…Consequently, of the 191 specimens reported in the literature, 45 specimens having less than 4 m in total length were juveniles, and 146 other specimens had a larger size, exceeding 4 m, were adults, the latter significantly outnumbered the former (χ 2 = 38.37, P < 0.05). Gubili et al (2010) sequenced mitochondrial DNA in four specimens of Mediterranean great white sharks, collected from four different sites at different periods of the year, and noted that juvenile sequences were identical. Gubili et al (2010) showed little genetic differentiation from Indo-Pacific lineages, but strong separation from geographically closer Atlantic and western Indian Ocean haplotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, of the 191 specimens reported in the literature, 45 specimens having less than 4 m in total length were juveniles, and 146 other specimens had a larger size, exceeding 4 m, were adults, the latter significantly outnumbered the former (χ 2 = 38.37, P < 0.05). Gubili et al (2010) sequenced mitochondrial DNA in four specimens of Mediterranean great white sharks, collected from four different sites at different periods of the year, and noted that juvenile sequences were identical. Gubili et al (2010) showed little genetic differentiation from Indo-Pacific lineages, but strong separation from geographically closer Atlantic and western Indian Ocean haplotypes.…”
mentioning
confidence: 99%
“…Gubili et al (2010) sequenced mitochondrial DNA in four specimens of Mediterranean great white sharks, collected from four different sites at different periods of the year, and noted that juvenile sequences were identical. Gubili et al (2010) showed little genetic differentiation from Indo-Pacific lineages, but strong separation from geographically closer Atlantic and western Indian Ocean haplotypes. These observations suggest that an isolated Mediterranean population of white sharks remains a justified hypothesis.…”
mentioning
confidence: 99%
“…Nonetheless, genetic analysis of Australian white shark populations suggests estimates of contemporary effective population sizes approach levels at which adaptive potential may be lost (Blower et al 2012). A similar concern was expressed following the observation that several contemporary white sharks sampled from across the Mediterranean all had the same Pacific clade mitochondrial haplotype (Gubili et al 2011). In Turkish waters white sharks are considered extinct in the Sea of Marmara, although contemporary records of neonates in the northern Aegean Sea suggest nearby breeding grounds (Kabasakal 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, each overlap contained only a single polymorphic site, the remaining amplicons allowing adequate haplotypic assignment (Pardini et al 2001). Two additional primers were designed to target polymorphisms diagnostic of potential Atlantic haplotypes as distinct from those of Mediterranean or Pacific origin (Gubili et al 2011). Of these, only one (D-loop7) was successfully used in this analysis, yielding a 206 bp product.…”
Section: Mtdna Analysesmentioning
confidence: 99%
See 1 more Smart Citation